Management Control System and Export Performance in an Indonesian Essential-Oil Exporter - Azka Salsabila Ramadhanti; Purwatiningsih Lisdiono (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2026)
This study investigates how a management control system (MCS) package supports export performance at PT Bentang Alam Sumatra (PT BAS), a community-based patchouli-oil exporter in North Sumatra that has experienced declining export volumes between 2023 and mid-2025. Using Malmi and Brown’s MCS-as-a-package framework, the research explores the design and use of planning, cybernetic, reward and compensation, administrative, and cultural controls in managing farmer partnerships, production processes, and export order fulfilment. A single-case study design is employed, drawing on semi-structured interviews with key managers and staff, non-participant observations, and internal company documents, which are analysed through thematic coding and a diagnostic matrix. The findings show that all five control elements are present, but their formalisation and linkage to export indicators are uneven. Building on this diagnosis, the study develops an as-is–to-be roadmap that proposes incremental to strengthen the coherence of the MCS package, enhance visibility of export performance, and better align BAS’s strategy.